Impact of invasive marmosets (Primates, Callitrichidae) on bird acoustic diversity in a large neotropical urban forest - Zaluar, Marina T.; Tardin, Rodrigo; Llusia, Diego; Niemeyer, Julia; Ribeiro, Milton C. [UNESP]; Vale, Mariana M. (Springer Nature, 2022)
Documenting the impacts of invasive species on native fauna is challenging and novel remote techniques may contribute to this urgent task. Two primate species, Callithrix jacchus and Callithrixpenicillata, have become invasive in the Brazilian Atlantic Forest, and are considered a threat to native birds, although very few studies have directly addressed their effect on the local communities. Here we used passive acoustic monitoring and acoustic diversity indices to identify (1) the environmental determinants of the occurrence of the marmosets and (2) the potential impact of these invasive species on the bird communities in a large urban forest (Tijuca Forest, Rio de Janeiro, Brazil). We found that invasive marmosets are associated with forest edges and disturbed areas (characterized by fewer woody lianas and presence of jackfruit trees). More importantly, the invasive marmosets occurrence (after removing the effect of their environmental determinants) was negatively related to the acoustic diversity of the bird dawn choruses, as measured by four out of six commonly used acoustic indices (ACI, ADI, H and NDSI). Our results suggest that these primate species impact on bird communities, although the mechanism behind the reduced acoustic diversity remains unclear (e.g., a consequence of direct predation, a shift on bird signaling behavior as an antipredator strategy, or both). This is one of the first studies to document the effect of marmosets Atlantic Forest bird community and to combine the use of passive acoustics and acoustic indices to address invasive species impacts on biodiversity, a promising approach for biological invasions research.
Keywords: Bioacoustics; Brazil; Fear ecology; Tijuca Forest